Diagnostic performance of C-TIRADS in malignancy risk stratification of thyroid nodules: A systematic review and meta-analysis - Hu, Yan; Xu, Shangyan; Zhan, Weiwei (Frontiers in Endocrinology, 2022)
Background Chinese thyroid imaging reports and data systems (C-TIRADS) is a novel malignancy risk stratification used for thyroid nodule diagnosis and guiding thyroid fine needle aspiration (FNA). In this review, we aim to assess the performance of C-TIRADS in malignancy risk stratification of thyroid nodules. Methods PubMed, Medline, Web of Science, Embase, CNKI and Wanfang data were searched until April 1st, 2022. Original articles reporting data about C-TIRADS and setting FNA or histology as reference standards were included. C-TIRADS 4A, 4B, 4C were set as thresholds respectively to obtain pooled sensitivity, specificity, positive likelihood ratio (LR+), negative likelihood ratio (LR-), diagnostic odds ratio (DOR), and the area under the curve (AUC). Integrated nested Laplace approximation was used for Bayesian bivariate meta-analysis of diagnostic tests. Results Sixteen studies were included, evaluating 11506 thyroid nodules. The rate of malignancy in each risk classification is comparable with that in C-TIRADS. C-TIRADS 4B appeared to have a better diagnostic performance than C-TIRADS 4A and 4C. The pooled sensitivity, specificity, LR+, LR-, DOR of C-TI-RADS 4B were 0.94 (95% CI: 0.89-0.97), 0.70 (95% CI: 0.60-0.79), 3.20 (95% CI: 2.28-4.39), 0.09 (95% CI: 0.05-0.15), 33.71 (95% CI: 25.51-42.40), respectively. The area under summary ROC curve was 0.94 (95% CI: 0.90-0.96). Conclusion C-TIRADS performed well in malignancy risk stratification of thyroid nodules. C-TIRADS 4B showed strong evidence of detecting malignancy.